Novel Excavation and Construction Method for a Deep Shaft Excavation in Ultrathick Aquifers - Chengyong Cao; Chenghua Shi; Linghui Liu; Jianwen Liu; Mingfeng Lei; Yuexiang Lin; Yichao Ye (Advances in Civil Engineering)
Dewatering using the dewatering systems composed of diaphragm walls and pumping wells is commonly adopted for deep excavations that are undertaken in deep aquifers. However, dewatering can sometimes induce environmental problems, especially when diaphragm walls cannot effectively cut off the aquifers. This paper mainly presents an innovative excavation technique combining dewatering excavation and underwater excavation without drainage, which is employed for a deep shaft excavation in ultrathick aquifers (up to 60–70 m thick aquifer) in Fuzhou, China. The shaft excavation with the depth of 41.6 m below the ground surface (BGS) is divided into two major phases, that is, (1) the first part of the excavation (the depth of 23.6 m BGS) is conducted by the way of conventional dewatering and braced excavation (Phase I) and (2) the second excavation with the depth of 23.6 m to 41.6 m BGS is carried out by the novel underwater excavation without drainage technique (Phase II). Field monitoring results show that the ratios of maximum ground surface settlement δvm to the excavation depth He in this case ranged from 0.03% to 0.1%. Most of the ratios of maximum lateral wall deflection δhm to excavation depth He are less than 0.1%. All these results are lesser than that predicted by empirical methods, which also confirmed the applicability of this innovative excavation. Thus, this innovative solution can be applicable to other deep excavations that are undertaken in ultrathick aquifers, especially for the excavation of coarse sediments with high permeability.